Risks of Daily Living Activities on Related Disability - Putra, Ashar Nuzulul; Zuama Qomarania, Witri; Nugroho, Purwo Setiyo; Fitri, Adelina; Sabaruddin, Erny Elviany; Dhani, Ridho Muhammad (Media Kesehatan Masyarakat Indonesia, 2022)
Indonesian lost 6 days productive time in average because the disability of daily activities, that must be dealt with seriously because the effect of this problem is the declining quality of life of a person and will also cause a burden for country. This research is expected to be the key to understand and overcome the problems of disability in daily activities. The research used cross sectional design with a secondary data based of Indonesian Family Life Survey (IFLS) 5. The analysis in this study was logistic regression with samples aged >40 years who participated in data collection conducted by RAND with a total of 8185 respondents. Almost all variables examined in this study were statistically significant with disabilities, there were age (p = 0.000, OR = 2.996, 95%CI = 2.726 – 3.294), gender (p = 0.000, OR = 1.858, 95%CI = 1.693 – 2.039), marital status (p = 0.000, OR = 2.211, 95%CI = 1.997 – 2.448), employment status (p = 0.000, OR = 2.540, 95%CI = 2.321 – 2.780), arthritis status (p = 0.000, OR = 1.687, 95%CI = 1.482 – 1.919) and obesity (p = 0.000, OR = 1.345, 95%CI = 1.177 – 1.538). Only variable educational level that is not significant with disability (p=0,198). The target of disability management is prioritized at an older age by providing health education and assistance so that they can withstand the threat of daily disability and lead to an improvement in their quality of life.